DAMPAK PENDIDIKAN AGAMA ISLAM TERHADAP PERUBAHAN TINGKAH LAKU ANAK - Suharnis, Suharnis (Musawa: Journal for Gender Studies, 2018)
The results obtained in this study show that the role of Islamic education on moral formation in the Tinoka community shows that its role is very important in the formation of three aspects in the child namely: moral educator, morality as an effort to instill good human character based on the Qur'an an and as-Sunnah and instill individual education in the community and the efforts made by Islamic religious leaders in moral formation include by instilling the values ​​of Islamic teachings and motivating the community. The implication of this study is to face the globalization and free trade conditions, so quality and quantity are the main supporting things in an effort to increase the community's faith, therefore it is recommended to the government or religious leaders to intensify their formation or moral formation especially with Islamic teachings in society.